Low Risk Sharing with Many Assets - Emile A. Marin; Sanjay R. Singh (University of California, Department of Economics, 2023)
Classical contributions in international macroeconomics rely on goods-market mechanisms to reconcile the cyclicality of real exchange rates when financial markets are incomplete. However, cross-border trade in one domestic and one foreign-currency-denominated risk-free asset prohibits these mechanisms from breaking the pattern consistent with complete markets. In this paper, we characterize how goods markets drive exchange rate cyclicality, taking into account trade in risk-free and/or risky assets. We show that goods-market mechanisms come back into play, even when there is cross-border trade in two risk-free assets, as long as we allow for empirically plausible heterogeneity in the stochastic discount factors of domestic marginal investors.
Keywords: E32; F31; F44; G15; 330; risk sharing; incomplete markets; exchange rates; Portfolio-Management; Internationaler Finanzmarkt; Risikomanagement; Wechselkurs; Zyklisches Verhalten; Zwei-Länder-Modell